Requirements elicitation and system design for a dyslexia online assessment and assistance / Aznoora Osman ... [et al.] - Osman, Aznoora; Ahmad Tarmizy, Nurul Azni Athirah; Abdul Wahab, Nadia; Md. Ilyas, Siti Sarah; Ibrahim, Norfiza (UiTM Cawangan Perlis, 2024)
In this paper, we discuss the requirements elicitation for a web-based system that provides a dyslexia early screening test and dyslexia information resources. Related works such as screening tool and websites were reviewed in order to highlight their key features and functionalities. This information was used to guide the suitable functional and non-functional requirements for the online assessment and assistance which would serve the interest of the educators, parents, individuals with dyslexia and system administrators who would be responsible in the system operation and maintenance. The screening tool was designed by adapting the Instrumen Senarai Semak Disleksia (ISD) that has already been used by teachers in Malaysian schools to identify if a child has high or low probability of having dyslexic. The result from the test would determine if a child needs further examination by medical practitioner and registration in special education inclusive program.